Bicomponent fibers comprising ethylene / alpha-olefin interpolymers

By adopting a core-sheath configuration bicomponent fiber, using the combination of the first and second ethylene/α-olefin interpolymers, the bicomponent fibers and nonwovens are solved in spinability, mechanical properties and recyclability in bicomponent fibers. Comprehensive optimization problems in terms of performance have achieved efficient fiber production and improvement of nonwoven performance.

CN115516142BActive Publication Date: 2025-02-18DOW GLOBAL TECHNOLOGIES LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180033440.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-08
Filing Date
2021-05-06
Publication Date
2025-02-18
Estimated Expiration
2041-05-06

AI Technical Summary

Technical Problem

Recyclability, flexibility, tensile strength, wear resistance and nonwovens made of highly spinable, fine denier bicomponent fibers and nonwovens made of such fibers are difficult to achieve nonwovens’ recyclability, softness, tensile strength, wear resistance and Comprehensive optimization of elongation at break.

Method used

The chemical and physical properties of the fibers are optimized by the core-sheath configuration arrangement using a two-component fiber containing the core region of the first ethylene/α-olefin interpolymer and the sheath region of the second ethylene/α-olefin interpolymer. .

Benefits of technology

The high spinning and excellent mechanical properties of the two-component fibers are achieved, including enhanced tensile strength, wear resistance and elongation of break, while ensuring the recyclability of the nonwovens.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115516142B_ABST
    Figure CN115516142B_ABST
Patent Text Reader

Abstract

Provided is a bicomponent fiber. The bicomponent fiber comprises a first region and a second region. The first region comprises a first ethylene / α-olefin interpolymer, and the second region comprises a second ethylene / α-olefin interpolymer. The highest peak melting temperature (Tm) of the first ethylene / α-olefin interpolymer is less than 130°C and at least 3.5°C greater than the highest peak melting temperature of the second ethylene / α-olefin interpolymer. The bicomponent fiber can be used to form a nonwoven fabric with improved tensile strength, elongation at break and / or abrasion resistance in various aspects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure are generally directed to bicomponent fibers comprising ethylene / α-olefin interpolymers, and nonwovens comprising the fibers. Background Art

[0002] Bicomponent fiber is the fiber that is made up of two different zones and corresponding polymer composition, and this polymer composition is extruded from the same spinneret, and wherein contains these two compositions in the same filament or fiber.When fiber leaves spinneret, this fiber is made up of non-mixed components that melt at the interface.Two polymer compositions can be different in its chemical and / or physical properties.Bicomponent fiber can be formed by spinning technology known in the art, and can be used to form nonwoven.The nonwoven formed by bicomponent fiber can have the property similar or different with the nonwoven formed by monocomponent fiber.However, there is a problem when developing high spinnability, fine denier bicomponent fiber and the nonwoven made by this type of bicomponent fiber, and this nonwoven is recyclable and has the combination of outstanding softness, tensile strength, abrasion resistance and / or elongation at break. Summary of the invention

[0003] Embodiments of the present disclosure provide bicomponent fibers that are strong and highly spinnable in all respects, as represented by high filament speed and low denier. Bicomponent fibers can be used to form nonwovens that are compatible with polyethylene recycling streams and can have a combination of enhanced tensile strength, abrasion resistance and / or elongation at break. The bicomponent fibers include a first region comprising a first ethylene / alpha-olefin interpolymer and a second region comprising a second ethylene / alpha-olefin interpolymer.

[0004] A bicomponent fiber is disclosed herein. The bicomponent fiber comprises a first region and a second region; the first region comprises a first ethylene / α-olefin interpolymer having a maximum peak melting temperature (Tm) less than 130°C; the second region comprises a second ethylene / α-olefin interpolymer having a density less than the density of the first ethylene / α-olefin interpolymer composition; wherein the maximum peak melting temperature (Tm) of the first ethylene / α-olefin interpolymer is at least 3.5°C greater than the maximum peak melting temperature (Tm) of the second ethylene / α-olefin interpolymer; wherein the first region and the second region are arranged in a core-sheath configuration.

[0005] A nonwoven is also disclosed herein. The nonwoven is formed by the bicomponent fibers disclosed herein. In an embodiment, the nonwoven has one or more of the following properties: a fiber denier equal to or less than 1.5 g / 9000 m; a tensile strength of greater than 11.0 Newtons / inch in the longitudinal direction at 20 grams / square meters (gsm) of the nonwoven; an elongation at break of greater than 100% in the longitudinal direction at 20 gsm of the nonwoven; and a tensile strength of less than 0.18 mg / cm in the longitudinal direction at 20 gsm of the nonwoven. 2 In an embodiment, the nonwoven formed from the bicomponent fibers disclosed herein has an elution curve achieved via an improved comonomer composition distribution (ICCD) procedure at 40.0°C to 68.0°C (WT 40℃-68℃ ), wherein the weight percent at a temperature range of 40.0°C to 68.0°C on an elution curve achieved via ICCD can be measured according to the test method described below.

[0006] Additional features and advantages of the embodiments will be set forth in the detailed description that follows, and will in part be readily apparent to those skilled in the art from that description or recognized by practicing the embodiments described herein, including the detailed description that follows, the claims, and the accompanying drawings.

[0007] It should be understood that the above and following descriptions describe various embodiments and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments, and are incorporated into and constitute a part of this specification. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 It is a schematic diagram of the single reactor data flow diagram.

[0009] Figure 2 It is a schematic diagram of the dual reactor data flow diagram.

[0010] Figure 3 is the ICCD elution curve of the nonwoven Example 2 of the present invention, which shows the temperature between 40.0°C and 68.0°C (WT 40℃-68℃ ) in the temperature range of T (T). DETAILED DESCRIPTION

[0011] The various aspects of the disclosed bicomponent fibers will be described in more detail below. Bicomponent fibers can be used to form nonwovens, and such nonwovens can have a variety of applications, including, for example, wipes, face masks, tissues, bandages, medical gowns, baby diapers, adult incontinence, and other medical and sanitary products. However, it should be noted that this is merely an illustrative implementation of the embodiments disclosed herein. These embodiments are applicable to other technologies susceptible to similar problems discussed above.

[0012] As used herein, the terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not these are specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any component, step, or procedure not specifically recited or listed.

[0013] As used herein, the term "interpolymer" refers to polymers prepared by polymerizing at least two different types of monomers. The term interpolymer thus includes copolymers (used to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.

[0014] As used herein, the term "polymer" means a polymeric compound prepared by polymerizing monomers, whether of the same or different types. The term polymer thus encompasses the term homopolymer (used to refer to polymers prepared from only one type of monomer, with the understanding that trace amounts of impurities may be incorporated into the polymer structure) and the term interpolymer as defined below. The polymer may be a single polymer or a polymer blend.

[0015] As used herein, the terms "nonwoven," "nonwoven web," and "nonwoven fabric" are used interchangeably herein. "Nonwoven" refers to a web or fabric having a structure of individual fibers or threads that are randomly interlaced rather than in an identifiable pattern as in a knitted fabric.

[0016] As used herein, the term "spunbond" refers to the manufacture of a nonwoven fabric comprising the following steps: (a) extruding molten thermoplastic strands from a plurality of fine capillaries called spinnerets; (b) quenching the strands with a generally cooled air stream to accelerate solidification of the molten strands; (c) attenuating the strands by advancing them through a quenching zone having a stretching tension, which may be applied by pneumatically clamping the strands in an air stream or by wrapping the strands around mechanical stretching rollers of the type commonly used in the textile fiber industry; (d) collecting the stretched strands as a web on a foraminous surface (e.g., a moving screen or porous strip); and (e) bonding the web of loose strands into a nonwoven fabric. Bonding may be achieved by a variety of means, including but not limited to thermal calendering processes, adhesive bonding processes, hot air bonding processes, needle punching processes, hydroentanglement processes, and combinations thereof.

[0017] As used herein, the term "meltblown" refers to the manufacture of nonwoven fabrics via a process generally comprising the following steps: (a) extruding molten thermoplastic strands from a spinneret; (b) using a high velocity heated air stream just below the spinneret while quenching and attenuating the polymer stream; (c) collecting the stretched strands as a web on a collecting surface. Meltblown webs can be bonded by a variety of means, including but not limited to autogenous bonding (i.e., self-bonding without further processing), thermal calendering processes, adhesive bonding processes, hot air bonding processes, needle punching processes, hydroentanglement processes, and combinations thereof.

[0018] A bicomponent fiber may comprise a combination of two or more suitable embodiments as disclosed herein.

[0019] A nonwoven formed from bicomponent fibers may comprise a combination of two or more suitable embodiments as disclosed herein.

[0020] fiber

[0021] According to the bicomponent fiber of the embodiment of the present disclosure, fiber can be formed via different technologies (for example, via melt spinning).In melt spinning, the first region and the second region can be melted, coextruded and forced to pass through the fine hole mouth in the metal plate, spinneret, enter air or other gases, wherein the coextruded region is cooled and solidified to form a bicomponent fiber.Solidified filaments can be extracted via air nozzle, rotating roller or godet roller, and can be laid on a conveyor belt as a mesh to form a nonwoven.According to the bicomponent fiber of the embodiment of the present disclosure, two regions (that is, the first region and the second region) are contained.The region can be configured with a core-sheath configuration (i.e., concentric core-sheath or island-in-the-sea configuration mentioned herein).For example, in an embodiment, the first region and the second region are arranged with a concentric core-sheath configuration, wherein the first region is a core region, and the second region is a sheath region, and the sheath region surrounds the core region. In other embodiments, the first region and the second region are arranged in a core-sheath, island-in-sea configuration, wherein the first region is a plurality of core regions (also referred to as islands), and the second region is a sheath region (also referred to as a sea), and the sheath region or the sea surrounds a plurality of core regions or islands.

[0022] In an embodiment, the bicomponent fiber comprises a first region and a second region, wherein the weight ratio of the first region to the second region is from 10:90 to 90:10. All individual values ​​and subranges of the ratio from 90:10 to 10:90 are disclosed and included herein. For example, in an embodiment, the weight ratio of the first region to the second region may be from 80:20 to 20:80, 70:30 to 30:70, 60:40 to 40:60, or 55:45 to 45:55.

[0023] In an embodiment, the bicomponent fiber has a denier of less than 50 g / 9000 m. All individual values ​​and subranges less than 50 g / 9000 m are disclosed and included herein. For example, the bicomponent fiber may have a denier of less than 40 g / 9000 m, less than 30 g / 9000 m, less than 20 g / 9000 m, less than 10 g / 9000 m, less than 5 g / 9000 m, less than 3 g / 9000 m, less than 2 g / 9000 m, less than 1.5 g / 9000 m, or less than 1.2 g / 9000 m, or the denier may be in the range of 0.1 g / 9000 m to 50 g / 9000 m, 0.1 g / 9000 m to 40 g / 9000 m, 0.1 g / 9000 m to 30 g / 9000 m, 0.1 g / 9000 m to 20 g / 9000 m, 0.1 g / 9000 m to 10 g / 9000 m, 0.1 g / 9000 m to 5 g / 9000 m, 0.1g / 9000m to 2.0g / 9000m, 0.1g / 9000m to 1.5g / 9000m, 0.1g / 9000m to 1.2g / 9000m, 1g / 9000m to 50g / 9000m, 1g / 9000m to 40g / 9000m, 1g / 9000m to 30g / 9000m, 1g / 9000m to The denier may be measured according to the test method described below.

[0024] First Area

[0025] The first region of the bicomponent fiber comprises a first ethylene / α-olefin interpolymer.

[0026] In an embodiment, the first region of the bicomponent fiber comprises, based on the total weight of the first region, an amount of at least 50 weight percent (wt%) of the first ethylene / α-olefin interpolymer. All individual values ​​and subranges of at least 50 wt% are disclosed and included herein. For example, in an embodiment, the first region may comprise, based on the total weight of the first region, an amount of at least 50 wt%, at least 60 wt%, at least 75 wt%, at least 85 wt%, at least 90 wt%, at least 95 wt%, or at least 99 wt% of the first ethylene / α-olefin interpolymer. In other embodiments, the first region can comprise the first ethylene / α-olefin interpolymer in an amount from 50 to 100 wt%, 60 to 100 wt%, 75 to 100 wt%, 85 to 100 wt%, 90 to 100 wt%, 95 to 100 wt%, 99 to 100 wt%, 50 to 95 wt%, 60 to 95 wt%, 75 to 95 wt%, 85 to 95 wt%, or 90 to 95 wt%, based on the total weight of the first region.

[0027] The term "ethylene / α-olefin interpolymer" refers to a polymer comprising ethylene and an α-olefin having 3 or more carbon atoms. In an embodiment, the first ethylene / α-olefin interpolymer comprises greater than 55 weight percent of units derived from ethylene and less than 45 weight percent of units derived from one or more α-olefin comonomers (based on the total amount of polymerizable monomers). All individual values ​​and subranges for greater than 55 weight percent of units derived from ethylene and less than 45 weight percent of units derived from one or more α-olefin comonomers are included and disclosed herein. For example, in embodiments, the first ethylene / α-olefin interpolymer may comprise (a) greater than 55%, greater than 70%, greater than 85%, greater than 90%, greater than 92%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, greater than 99.5%, or from 55% to 99.5%, from 55% to 95%, from 55% to 90%, from 55% to 99.5%, from 55% to 99%, from 55% to 97%, from 55% to 94%, from 75% to 90%, from 90% to 99.9%, from 90% to 99.5%, from 90% to 97%, or from 90% to 95% by weight of an olefin derived from % to 20%, 1% to 10%, 1% to 5%, 5% to 20%, or 5% to 10% by weight of units derived from one or more alpha-olefin comonomers. The comonomer content can be measured using any suitable technique, such as techniques based on nuclear magnetic resonance ("NMR") spectroscopy, and for example by measuring the amount of alpha-olefin comonomers as described in U.S. Pat. No. 7,498,282. 13 CNMR analysis, which is incorporated herein by reference.

[0028] Suitable α-olefin comonomers typically have no more than 20 carbon atoms. The one or more α-olefins of the first ethylene / α-olefin interpolymer may be selected from the group consisting of: C3-C20 acetylenically unsaturated monomers and C4-C18 dienes. For example, the α-olefin comonomer may have 3 to 10 carbon atoms or 3 to 8 carbon atoms. Exemplary α-olefin comonomers include, but are not limited to, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and 4-methyl-1-pentene. The one or more α-olefin comonomers of the first ethylene / α-olefin interpolymer may, for example, be selected from the group consisting of: propylene, 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of: 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of: 1-hexene and 1-octene. In one or more embodiments, the first ethylene / α-olefin interpolymer can comprise greater than 0 wt% and less than 45 wt% units derived from one or more of 1-octene, 1-hexene, or 1-butene comonomers.

[0029] In an embodiment, the density of the first ethylene / α-olefin interpolymer is 0.940 g / cm 3 Up to 0.965g / cm 3 This article discloses and includes 0.940g / cm 3 Up to 0.965g / cm 3 All individual values ​​and subranges of density within the range of . For example, the density of the first ethylene / α-olefin interpolymer can be 0.940 g / cm 3 Up to 0.965g / cm 3 , 0.940g / cm 3 Up to 0.960g / cm 3 , 0.945g / cm 3 Up to 0.965g / cm 3 , 0.945g / cm 3 Up to 0.960g / cm 3 、0.950g / cm 3 Up to 0.965g / cm 3 or 0.950g / cm 3 Up to 0.960g / cm 3 The density can be measured in accordance with ASTM D792.

[0030] In an embodiment, the melt index (I2) of the first ethylene / α-olefin interpolymer measured according to ASTM D1238, 190°C, 2.16kg is in the range of 10 g / 10 min to 60 g / 10 min. All individual values ​​and subranges of 10 g / 10 min to 60 g / 10 min are included and disclosed herein. For example, in some embodiments, the melt index (I2) of the first ethylene / α-olefin interpolymer may be 10 g / 10 min to 60 g / 10 min, 10 g / 10 min to 50 g / 10 min, 10 g / 10 min to 40 g / 10 min, 10 g / 10 min to 30 g / 10 min, 10 g / 10 min to 20 g / 10 min, 20 g / 10 min to 6 ... The melt index (I2) may be in the range of 15 to 20 g / 10 min, 20 to 40 g / 10 min, 20 to 30 g / 10 min, 15 to 60 g / 10 min, 15 to 50 g / 10 min, 15 to 40 g / 10 min, 15 to 30 g / 10 min or 15 to 20 g / 10 min, wherein the melt index (I2) may be measured according to ASTM D1238, 190°C, 2.16 kg.

[0031] In an embodiment, the molecular weight distribution of the first ethylene / α-olefin interpolymer is determined by conventional gel permeation chromatography (GPC) and is expressed as a ratio of weight average molecular weight to number average molecular weight (M) ranging from 1.5 to 5.0. w(GPC) / M n(GPC) ). The present invention discloses and includes a molecular weight distribution (M) of 1.5 to 5.0. w(GPC) / M n(GPC) ) all individual values ​​and subranges. For example, the molecular weight distribution (M) of the first ethylene / α-olefin interpolymer is w(GPC) / M n(GPC) ) may be 1.5 to 5.0, 1.5 to 4.0, 1.5 to 3.0, 1.5 to 2.5, 2.0 to 5.0, 2.0 to 4.0, 2.0 to 3.0, or 2.0 to 2.5, wherein the molecular weight distribution (M) may be measured according to the conventional GPC test method described below. w(GPC) / M n(GPC) ).

[0032] In an embodiment, the first region may include additional components, such as one or more other polymers and / or one or more additives. The other polymers may include another ethylene / α-olefin interpolymer, a polymer recycled after consumption or after industry, a polyester, a propylene-based polymer (e.g., a polypropylene homopolymer, a propylene-ethylene copolymer, or a propylene / α-olefin interpolymer), or a propylene-based plastomer or elastomer. Based on the total weight of the first region, the amount of the other polymers may be up to 50 wt%. For example, in an embodiment, the first region may include up to 50 wt% of a propylene-based plastomer or a propylene-based elastomer (such as VERSIFY available from The Dow Chemical Company). TM Polymers and VISTAMAXX available from ExxonMobil Chemical Co. TM Polymers), low modulus and / or low molecular weight polypropylene (such as L-MODU from Idemitsu) TM Polymers), random copolymers of polypropylene or propylene-based olefin block copolymers (such as INTUNE TM Potential additives include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers, pigments, primary antioxidants, secondary antioxidants, processing aids, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, deodorants, antifungal agents, and combinations thereof. The first region may contain additives in an amount of about 0.01 or 0.1 or 1 to about 25 or about 20 or about 15 or about 10 or about 5 weight percent based on the total weight of the first region.

[0033] In an embodiment, the first ethylene / α-olefin interpolymer has a maximum peak melting temperature (Tm) of less than 130° C. when measured according to the Differential Scanning Calorimetry (DSC) test method described below. All individual values ​​and subranges less than 130° C. are disclosed and incorporated herein. For example, in an embodiment, the first ethylene / α-olefin interpolymer may have a maximum peak melting temperature (Tm) of less than 130° C., less than 129.5° C., less than 129° C., or less than 128.5° C., or may be in the range of 120° C. to 130° C., 125° C. to 130° C., 127° C. to 130° C., 128° C. to 130° C., 125° C. to 129.5° C., 126° C. to 129° C., 126° C. to 128° C., 127° C. to 129° C., 127° C. to 128.5° C., or 127° C. to 128° C. when measured according to the DSC test method described below.

[0034] In an embodiment, the highest peak crystallization temperature (Tc) of the first ethylene / α-olefin interpolymer is in the range of 108°C to 118°C, wherein the highest peak crystallization temperature (Tc) can be measured according to the DSC test method described below. All individual values ​​and subranges from 108°C to 118°C are disclosed and included herein. For example, when measured according to the DSC test method described below, the highest peak crystallization temperature (Tc) of the first ethylene / α-olefin interpolymer can be in the range of 108°C to 118°C, 110°C to 118°C, 112°C to 118°C, 108°C to 116°C, 108°C to 115°C, 110°C to 116°C, 110°C to 115°C, 112°C to 116°C, or 113°C to 115°C.

[0035] Second area

[0036] The second region of the bicomponent fiber comprises a second ethylene / α-olefin interpolymer.

[0037] In an embodiment, the second region of the bicomponent fiber comprises a second ethylene / α-olefin interpolymer in an amount of at least 50 weight percent (wt%) based on the total weight of the second region. All individual values ​​and subranges of at least 50 wt% are disclosed and included herein. For example, in an embodiment, the second region may comprise a second ethylene / α-olefin interpolymer in an amount of at least 50 wt%, at least 60 wt%, at least 75 wt%, at least 85 wt%, at least 90 wt%, at least 95 wt%, or at least 99 wt%, based on the total weight of the second region. In other embodiments, the second region can comprise the second ethylene / α-olefin interpolymer in an amount from 50 to 100 wt%, 60 to 100 wt%, 75 to 100 wt%, 85 to 100 wt%, 90 to 100 wt%, 95 to 100 wt%, 99 to 100 wt%, 50 to 95 wt%, 60 to 95 wt%, 75 to 95 wt%, 85 to 95 wt%, or 90 to 95 wt%, based on the total weight of the second region.

[0038] In an embodiment, the second ethylene / α-olefin interpolymer comprises greater than 55 weight percent units derived from ethylene and less than 45 weight percent units derived from one or more α-olefin comonomers (based on the total amount of polymerizable monomers). All individual values ​​and subranges for greater than 55 weight percent units derived from ethylene and less than 45 weight percent units derived from one or more α-olefin comonomers are included and disclosed herein. For example, the second ethylene / α-olefin interpolymer may comprise (a) greater than 55%, greater than 70%, greater than 85%, greater than 90%, greater than 92%, greater than 95%, greater than 97%, greater than 98%, greater than 99%, greater than 99.5%, or from 55% to 99.5%, from 55% to 95%, from 55% to 90%, from 55% to 99.5%, from 55% to 99%, from 55% to 99.5%, from 55% to 99%, from 55% to 97%, from 55% to 94%, from 75% to 90%, from 90% to 99.9%, from 90% to 99.5%, from 90% to 97%, or from 90% to 95% by weight of monomers derived from ethylene. and (b) less than 45%, less than 30%, less than 20%, less than 18%, less than 15%, less than 12%, less than 10%, less than 8%, less than 5%, less than 4%, less than 3%, less than 2%, less than 1%, or 0.1% to 45%, 0.1% to 25%, 0.1% to 10%, 0.1% to 5%, 0.5% to 20%, 0.5% to 10%, 0.5% to 5%, 1% to 20%, 1% to 10%, 1% to 5%, 5% to 20%, or 5% to 10% by weight of units derived from one or more alpha-olefin comonomers. Comonomer content can be measured using any suitable technique, such as techniques based on nuclear magnetic resonance ("NMR") spectroscopy, and for example by as described in U.S. Pat. No. 7,498,282 13 C NMR analysis, which is incorporated herein by reference.

[0039] Suitable α-olefin comonomers typically have no more than 20 carbon atoms. The one or more α-olefins of the second ethylene / α-olefin interpolymer may be selected from the group consisting of: C3-C20 acetylenically unsaturated monomers and C4-C18 dienes. For example, the α-olefin comonomer may have 3 to 10 carbon atoms or 3 to 8 carbon atoms. Exemplary α-olefin comonomers include, but are not limited to, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and 4-methyl-1-pentene. The one or more α-olefin comonomers of the second ethylene / α-olefin interpolymer may, for example, be selected from the group consisting of: propylene, 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of: 1-butene, 1-hexene, and 1-octene; or in the alternative, selected from the group consisting of: 1-hexene and 1-octene. In one or more embodiments, the second ethylene / α-olefin interpolymer can comprise greater than 0 wt% and less than 45 wt% units derived from one or more of 1-octene, 1-hexene, or 1-butene comonomers.

[0040] In an embodiment, the density of the second ethylene / α-olefin interpolymer is less than the density of the first ethylene / α-olefin interpolymer. In an embodiment, the density of the first ethylene / α-olefin interpolymer is at least 0.022 g / cm greater than the density of the second ethylene / α-olefin interpolymer. 3 This article includes and discloses at least 0.022 g / cm 3 For example, the density of the first ethylene / α-olefin interpolymer can be at least 0.022 g / cm greater than the density of the second ethylene / α-olefin interpolymer. 3 , 0.025g / cm 3 , 0.027g / cm 3 , 0.029g / cm 3 , 0.031g / cm 3 , 0.033g / cm 3 , 0.035g / cm 3 , 0.037g / cm 3 , 0.039g / cm 3 or 0.041 g / cm 3 , wherein the density can be measured according to ASTM D792. In other embodiments, the difference between the density of the first ethylene / α-olefin interpolymer and the density of the second ethylene / α-olefin interpolymer is within 0.023 g / cm 3 Up to 0.085g / cm 3 , 0.023g / cm 3 Up to 0.050g / cm 3 , 0.023g / cm3 to 0.040g / cm 3, 0.029g / cm 3 Up to 0.085g / cm 3 , 0.029g / cm 3 Up to 0.050g / cm 3 , 0.031g / cm 3 Up to 0.085g / cm 3 , 0.031g / cm 3 Up to 0.050g / cm 3 , 0.031g / cm 3 Up to 0.040g / cm 3 , 0.039g / cm 3 Up to 0.050g / cm 3 or 0.039 g / cm 3 Up to 0.085g / cm 3 The density can be measured in accordance with ASTM D792.

[0041] In an embodiment, the density of the second ethylene / α-olefin interpolymer is 0.880 g / cm 3 Up to 0.940g / cm 3 This article discloses and includes 0.880g / cm 3 Up to 0.940g / cm 3 All individual values ​​and subranges of density within the range of . For example, in some embodiments, the density of the second ethylene / α-olefin interpolymer may be between 0.880 cm 3 Up to 0.940g / cm 3 、0.880g / cm 3 Up to 0.930g / cm 3 、0.880g / cm 3 Up to 0.920g / cm 3 、0.890g / cm 3 Up to 0.940g / cm 3 、0.890g / cm 3 Up to 0.930g / cm 3 、0.890g / cm 3 Up to 0.920g / cm 3 、0.890g / cm 3 Up to 0.910g / cm 3 , 0.900g / cm 3 Up to 0.940g / cm 3 , 0.900g / cm 3 Up to 0.930g / cm 3 , 0.900g / cm 3 Up to 0.920g / cm 3or 0.900g / cm 3 Up to 0.910g / cm 3 The density can be measured in accordance with ASTM D792.

[0042] In an embodiment, the melt index (I2) of the second ethylene / α-olefin interpolymer measured according to ASTM D1238, 190°C, 2.16kg is in the range of 10 g / 10 min to 60 g / 10 min. All individual values ​​and subranges of 10 g / 10 min to 60 g / 10 min are included and disclosed herein. For example, in some embodiments, the melt index (I2) of the second ethylene / α-olefin interpolymer may be 10 g / 10 min to 60 g / 10 min, 10 g / 10 min to 50 g / 10 min, 10 g / 10 min to 40 g / 10 min, 10 g / 10 min to 30 g / 10 min, 10 g / 10 min to 20 g / 10 min, 20 g / 10 min to 6 ... The melt index (I2) may be in the range of 15 to 20 g / 10 min, 20 to 40 g / 10 min, 20 to 30 g / 10 min, 15 to 60 g / 10 min, 15 to 50 g / 10 min, 15 to 40 g / 10 min, 15 to 30 g / 10 min or 15 to 20 g / 10 min, wherein the melt index (I2) may be measured according to ASTM D1238, 190°C, 2.16 kg.

[0043] In an embodiment, the second ethylene / α-olefin interpolymer has a molecular weight distribution, expressed as a ratio of weight average molecular weight to number average molecular weight (M) from 1.5 to 5.0. w(GPC) / M n(GPC) ). The present invention discloses and includes a molecular weight distribution (M) of 1.5 to 5.0. w(GPC) / M n(GPC) ) all individual values ​​and subranges. For example, the molecular weight distribution (M) of the second ethylene / α-olefin interpolymer is w(GPC) / M n(GPC) ) may be 1.5 to 5.0, 1.5 to 4.0, 1.5 to 3.0, 1.5 to 2.5, 2.0 to 5.0, 2.0 to 4.0, 2.0 to 3.0, or 2.0 to 2.5, wherein the molecular weight distribution (M ) may be measured according to conventional gel permeation chromatography (GPC) test methods described below. w(GPC) / M n(GPC) ).

[0044] In an embodiment, the second region may include additional components, such as one or more other polymers and / or one or more additives. The other polymers may include another ethylene / α-olefin interpolymer, polyester, post-consumer or post-industrial recycled polymer, propylene-based polymer (e.g., polypropylene homopolymer, propylene-ethylene copolymer or propylene / α-olefin interpolymer) or propylene-based plastomers or elastomers. Based on the total weight of the second region, the amount of other polymers may be up to 50 wt%. For example, in an embodiment, the second region may include up to 50 wt% of propylene-based plastomers or propylene-based elastomers (such as VERSIFY available from Dow Chemical Company). TM Polymers and VISTAMAXX available from ExxonMobil Chemical Company TM Polymers), low modulus and / or low molecular weight polypropylene (such as L-MODU TM Polymers), random copolymers of polypropylene or propylene-based olefin block copolymers (such as INTUNE TM ). Potential additives include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers, pigments, primary antioxidants, secondary antioxidants, processing aids, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, deodorants, antifungal agents, and combinations thereof. The second region may contain additives in an amount of about 0.01 or 0.1 or 1 to about 25 or about 20 or about 15 or about 10 or about 5 weight percent based on the total weight of the second region.

[0045] In an embodiment, the highest peak melting temperature (Tm) of the first ethylene / α-olefin interpolymer is less than 130°C, and the highest peak melting temperature (Tm) of the first ethylene / α-olefin interpolymer is at least 3.5°C greater than the highest peak melting temperature (Tm) of the second ethylene / α-olefin interpolymer, wherein the highest peak melting temperature (Tm) can be measured according to the DSC test method described below. All individual values ​​and subranges of at least 3.5°C are disclosed and included herein. For example, in some embodiments, the highest peak melting temperature (Tm) of the first ethylene / α-olefin interpolymer is at least 3.5°C greater, at least 4.0°C greater, at least 4.5°C greater, or at least 5°C greater than the highest peak melting temperature (Tm) of the second ethylene / α-olefin interpolymer. In other embodiments, the difference between the highest peak melting temperature (Tm) of the first ethylene / α-olefin interpolymer and the highest peak melting temperature (Tm) of the second ethylene / α-olefin interpolymer is in the range of 3.5°C to 60°C, 4.0°C to 60°C, 4.5°C to 60°C, 5°C to 60°C, 3.5°C to 45°C, 4.0°C to 45°C, 5°C to 45°C, 3.5°C to 30°C, 4.0°C to 30°C, 4.5°C to 30°C, 5°C to 30°C, 3.5°C to 15°C, 4.0°C to 15°C, 4.5°C to 15°C, or 5°C to 15°C, where the highest peak melting temperature (Tm) can be measured according to the DSC test method described below.

[0046] In an embodiment, the second ethylene / α-olefin interpolymer has a maximum peak melting temperature (Tm) of less than 127.5° C. when measured according to the DSC test method described below. All individual values ​​and subranges less than 127.5° C. are disclosed and incorporated herein. For example, in an embodiment, the second ethylene / α-olefin interpolymer may have a maximum peak melting temperature (Tm) of less than 127° C., less than 126.5° C., less than 126° C., less than 125.5° C., less than 125° C., less than 124.5° C., less than 124° C., less than 123.5° C., or less than 123° C., or may be between 90° C. and 127.5° C., 100° C. and 127.5° C., 110° C. and 127.5° C., 12 ... ℃ to 126 ℃, 110 ℃ to 126 ℃, 120 ℃ to 126 ℃, 122 ℃ to 126 ℃, 90 ℃ to 124 ℃, 100 ℃ to 124 ℃, 110 ℃ to 124 ℃, 120 ℃ to 124 ℃ or 122 ℃ to 124 ℃, wherein the highest peak melting temperature (Tm) can be measured according to the DSC test method described below.

[0047] In an embodiment, the second ethylene / α-olefin interpolymer has a maximum peak crystallization temperature (Tc) in the range of 90°C to 114.5°C, wherein the maximum peak crystallization temperature (Tc) can be measured according to the DSC test method described below. All individual values ​​and subranges from 90°C to 114.5°C are disclosed and included herein. For example, the second ethylene / α-olefin interpolymer may have a maximum peak crystallization temperature (Tc) in the range of 90°C to 114.5°C, 90°C to 110°C, 90°C to 105°C, 95°C to 100°C, 95°C to 110°C, 95°C to 105°C, or 95°C to 100°C, 90°C to 114°C, 90°C to 113°C, or 90°C to 112°C, wherein the maximum peak crystallization temperature (Tc) can be measured according to the DSC test method described below.

[0048] In an embodiment, the first ethylene / α-olefin interpolymer has a maximum peak crystallization temperature (Tc) that is at least 3.5° C. greater than the maximum peak crystallization temperature (Tc) of the second ethylene / α-olefin interpolymer. All individual values ​​and subranges that are at least 3.5° C. greater are included and disclosed herein. For example, the maximum peak crystallization temperature (Tc) of the first ethylene / α-olefin interpolymer may be at least 3.5° C. greater, at least 5° C. greater, at least 7.5° C. greater, at least 10° C. greater, at least 11° C. greater, at least 15° C. greater, or at least 17° C. greater than the maximum peak crystallization temperature (Tc) of the second ethylene / α-olefin interpolymer, wherein the maximum peak crystallization temperature (Tc) may be measured according to the DSC test method described below. In other embodiments, the difference between the highest peak crystallization temperature (Tc) of the first ethylene / α-olefin interpolymer and the highest peak crystallization temperature (Tc) of the second ethylene / α-olefin interpolymer is in the range of 3.5°C to 25°C, 5°C to 25°C, 10°C to 25°C, 15°C to 25°C, 3.5°C to 20°C, 5°C to 20°C, 10°C to 20°C, 15°C to 20°C, 3.5°C to 15°C, 5°C to 15°C, or 10°C to 15°C, wherein the highest peak crystallization temperature (Tc) can be measured according to the DSC test method described below.

[0049] Synthesis of the first or second ethylene / α-olefin interpolymer

[0050] Any conventional polymerization process may be used to produce the first or second ethylene / α-olefin interpolymer. Such conventional polymerization processes include, but are not limited to, solution polymerization processes using one or more conventional reactors (e.g., loop reactors in parallel, in series, isothermal reactors, stirred tank reactors, batch reactors, and / or any combination thereof). Such conventional polymerization processes also include gas phase, solution, or slurry polymerizations or any combination thereof using any type of reactor or reactor configuration known in the art.

[0051] In an embodiment, the solution phase polymerization process occurs in one or more well-stirred reactors, such as one or more loop reactors, at a temperature in the range of 115°C to 250°C; for example, at a temperature in the range of 155°C to 225°C, and at a pressure in the range of 300 to 1000 psi; for example, at a pressure of 400 psi to 750 psi. In one embodiment, in a dual reactor, the temperature in the first reactor temperature is in the range of 115°C to 190°C (e.g., 115°C to 170°C), and the second reactor temperature is in the range of 150°C to 210°C (e.g., 170°C to 205°C). In another embodiment, in a single reactor, the temperature in the reactor temperature is in the range of 115°C to 250°C (e.g., 155°C to 225°C). The residence time in the solution phase polymerization process is typically in the range of 2 minutes to 30 minutes; for example, in the range of 5 minutes to 20 minutes. Ethylene, solvent, one or more catalyst systems, optionally one or more cocatalysts, optionally one or more impurity scavengers and optionally one or more comonomers are continuously fed into one or more reactors. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents are commercially available under the name ISOPAR E from ExxonMobil Chemical Company in Houston, Texas. The resulting mixture of the first or second polyethylene composition and the solvent is then taken out from the reactor and the first or second polyethylene composition is separated. The solvent is typically recovered via a solvent recovery unit (i.e., a heat exchanger and a vapor liquid separator drum) and subsequently recycled back into the polymerization system.

[0052] In one embodiment, the first or second ethylene / α-olefin interpolymer may be produced via a solution polymerization process in a dual reactor system (e.g., a dual loop reactor system), wherein ethylene and optionally one or more α-olefins are polymerized in the presence of one or more catalyst systems. In addition, one or more cocatalysts may be present. In another embodiment, the first or second ethylene / α-olefin interpolymer may be produced via a solution polymerization process in a single reactor system (e.g., a single loop reactor system), wherein ethylene and optionally one or more α-olefins are polymerized in the presence of one or more catalyst systems.

[0053] An example of a catalyst system suitable for producing the first ethylene / α-olefin interpolymer may be a catalyst system comprising a major catalyst component comprising a metal-ligand complex of formula (I):

[0054]

[0055] In formula (I), M is a metal selected from titanium, zirconium or hafnium, the metal having a formal oxidation state of +2, +3 or +4; n is 0, 1 or 2; when n is 1, X is a monodentate ligand or a bidentate ligand; when n is 2, each X is a monodentate ligand and is the same or different; the metal-ligand complex as a whole is electrically neutral; each Z is independently selected from -O-, -S-, -N(R N )-or–P(R P )-, where each R N and R P are independently (C1-C30)alkyl or (C1-C30)heteroalkyl; L is (C1-C 40 )alkylene or (C1-C 40 )heteroalkylene, wherein (C1-C 40 ) the alkylene group has a moiety (to which L is bonded) comprising a 1-carbon atom to 10-carbon atom linker backbone connecting the two Z groups in formula (I), or (C1-C 40 ) heteroalkylene has a moiety comprising a 1-atom to 10-atom linker backbone connecting two Z groups in formula (I), wherein (C1-C 40 ) wherein each of the 1 to 10 atoms of the 1-atom to 10-atom connected main chain of the heteroalkylene group is independently a carbon atom or a heteroatom, wherein each heteroatom is independently O, S, S(O), S(O)2, Si(R C )2、Ge(R C 2. P(R C ) or N(R C ), where each R C Independently (C1-C 30 )alkyl or (C1-C 30 ) heteroalkyl; R 1 and R 8 Independently selected from the group consisting of: -H, (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2.-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(RN )2NC(O)-, halogen and a group having formula (II), formula (III) or formula (IV):

[0056]

[0057] In formula (II), (III) and (IV), R 31-35 , R 41-48 or R 51-59 Each of which is independently selected from (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2, -N=CHR C 、-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(R N )2NC(O)-, halogen or -H, provided that R 1 or R 8 At least one of them is a group having formula (II), formula (III) or formula (IV), wherein R C , R N and R P As defined above.

[0058] In formula (I), R 2-4 , R 5-7 and R 9-16 Each of which is independently selected from (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heteroalkyl, -Si(R C )3, -Ge(R C )3. -P(R P )2、-N(R N )2, -N=CHR C 、-OR C 、-SR C 、-NO2、-CN、-CF3、R C S(O)-、R C S(O)2-、(RC )2C=N-、R C C(O)O-、R C OC(O)-、R C C(O)N(R N )-、(R C )2NC(O)-, halogen and -H, where R C , R N and R P As defined above.

[0059] Catalyst systems comprising the metal-ligand complex of formula (I) may be rendered catalytically active by any technique known in the art for activating metal-based catalysts for olefin polymerization reactions. For example, the metal-ligand complex of formula (I) may be rendered catalytically active by contacting the complex with an activating cocatalyst or combining the complex with an activating cocatalyst. Activating cocatalysts suitable for use herein include alkylaluminums; polymeric or oligomeric aluminoxanes (also referred to as aluminoxanes); neutral Lewis acids; and non-polymeric, non-coordinating, ion-forming compounds (including the use of such compounds under oxidizing conditions). A suitable activation technique is bulk electrolysis. Combinations of one or more of the foregoing activating cocatalysts and techniques are also contemplated. The term "alkylaluminum" means a monoalkylaluminum dihydride or monoalkylaluminum dihalide, a dialkylaluminum hydride or dialkylaluminum halide, or a trialkylaluminum. Examples of polymeric or oligomeric aluminoxanes include methylaluminoxane, methylaluminoxane modified with triisobutylaluminum, and isobutylaluminoxane.

[0060] Lewis acid activators (cocatalysts) include those containing 1 to 3 (C1-C 20 ) hydrocarbyl substituent. Examples of Group 13 metal compounds are tri((C1-C 20 ) alkyl) substituted aluminum or tri((C1-C 20 ) alkyl)-boron compounds; tri(alkyl)-substituted aluminum, tri((C1-C 20 )alkyl)-boron compounds; tri((C1-C 10 )alkyl)aluminum, tri((C6-C 18 ) aryl) boron compounds; and halogenated (including perhalogenated) derivatives thereof. In another example, the Group 13 metal compound is tri(fluoro-substituted phenyl) borane, tri(pentafluorophenyl) borane. The activating cocatalyst may be tri((C1-C 20 ) alkyl borate (e.g., trityl tetrafluoroborate) or tris((C1-C 20 )alkyl)tetra((C1-C 20 As used herein, the term "ammonium" refers to a nitrogen cation that is ((C1-C 20)alkyl)4N + 、((C1-C 20 )alkyl)3N(H) + 、((C1-C 20 )alkyl)2N(H)2 + 、(C1-C 20 )Hydrocarbon N(H)3 + or N(H)4 + , where there are two or more (C1-C 20 ) hydrocarbon groups, each of which may be the same or different.

[0061] Combinations of neutral Lewis acid activators (cocatalysts) include mixtures comprising tri((C1-C4)alkyl)aluminum and tri((C6-C 18 The present invention also provides a combination of a neutral Lewis acid mixture with a polymeric or oligomeric aluminoxane, and a combination of a single neutral Lewis acid (especially tris(pentafluorophenyl)borane) with a polymeric or oligomeric aluminoxane. The ratio of the number of moles of (metal-ligand complex):(tris(pentafluoro-phenylborane):(aluminoxane) [e.g., (Group 4 metal-ligand complex):(tris(pentafluoro-phenylborane):(aluminoxane)] is 1:1:1 to 1:10:30, or 1:1:1.5 to 1:5:10.

[0062] The catalyst system comprising the metal-ligand complex of formula (I) can be activated by combining with one or more cocatalysts (e.g., cation forming cocatalysts, strong Lewis acids, or combinations thereof) to form an active catalyst composition. Suitable activating cocatalysts include polymeric or oligomeric aluminoxanes (especially methylaluminoxane) and inert, compatible, non-coordinating, ion forming compounds. Exemplary suitable cocatalysts include, but are not limited to, modified methylaluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyltetrakis(pentafluorophenyl)boric acid (1 - )amines and combinations thereof.

[0063] One or more of the aforementioned activating cocatalysts may be used in combination with one another. A preferred combination is a mixture of tri((C1-C4)hydrocarbyl)aluminum, tri((C1-C4)hydrocarbyl)borane or ammonium borate with an oligomeric or polymeric aluminoxane compound. The ratio of the total number of moles of one or more metal-ligand complexes of formula (I) to the total number of moles of one or more of the activating cocatalysts is from 1:10,000 to 100:1. The ratio may be at least 1:5000, or at least 1:1000; and may not exceed 10:1 or may not exceed 1:1. When aluminoxane is used alone as an activating cocatalyst, the number of moles of aluminoxane employed may preferably be at least 100 times the number of moles of the metal-ligand complex of formula (I). When tri(pentafluorophenyl)borane is used alone as an activating co-catalyst, the ratio of the number of moles of tri(pentafluorophenyl)borane employed to the total number of moles of the one or more metal-ligand complexes of formula (I) may be 0.5: 1 to 10: 1, 1: 1 to 6: 1, or 1: 1 to 5: 1. The remaining activating co-catalyst is typically employed in a molar amount approximately equal to the total molar amount of the one or more metal-ligand complexes of formula (I).

[0064] Nonwovens

[0065] Disclosed herein are nonwovens formed from the bicomponent fibers described above.

[0066] The nonwoven formed by the bicomponent fiber disclosed herein can be formed via different technologies. Such technologies for forming nonwovens by the bicomponent fiber disclosed herein include melt spinning, meltblowing process, spunbonding process, staple process, carding web process, air laid process (air laid process), thermal calendering process, adhesive bonding process, hot air bonding process, needle punching process, spunlace process and electrostatic spinning process. For example, in one embodiment, a spunbond nonwoven comprising the bicomponent fiber according to the embodiment disclosed herein can be formed. In other embodiments, a meltblown nonwoven comprising the bicomponent fiber according to the embodiment disclosed herein can be formed.

[0067] The nonwoven formed by the bicomponent fibers disclosed herein can have a combination of lower denier, enhanced tensile strength, enhanced abrasion resistance, and / or higher elongation at break. In one or more embodiments herein, the nonwoven can exhibit one or more of the following properties: a fiber denier equal to or less than 1.5 g / 9000 m (alternatively, equal to or less than 1.4 g / 9000 m, equal to or less than 1.3 g / 9000 m, or equal to or less than 1.2 g / 9000 m, or in the range of 0.8 g / 9000 m to 2 g / 9000 m, 1.0 g / 9000 m to 1.8 g / 9000 m, 1.0 g / 9000 m to 1.6 g / 9000 m, or 1.0 g / 9000 m to 1.4 g / 9000 m), wherein the fiber denier is measured according to the test method described below ; a tensile strength of greater than 11.0 Newtons per inch (N / 1 inch) (alternatively, greater than 13.0 N / 1 inch, greater than 15.0 N / 1 inch, or greater than 17.0 N / 1 inch, or in the range of 12.0 N / 1 inch to 25 N / 1 inch, 13.0 N / 1 inch to 25 N / 1 inch, 15.0 N / 1 inch to 25 N / 1 inch, or 18.0 N / 1 inch to 25 N / 1 inch) in the machine direction (MD) at 20 grams per square meter (gsm) of nonwoven, wherein the tensile strength is measured according to the test method described below; less than 0.18 mg / cm2 in the machine direction (MD) at 20 gsm nonwoven. 2 (Alternatively, less than 0.16 mg / cm 2 Less than 0.14mg / cm 2 Less than 0.12mg / cm 2 Less than 0.10mg / cm 2 Less than 0.08mg / cm 2 Less than 0.06mg / cm 2 , or at 0.01 mg / cm 2 Up to 0.16mg / cm 2 , 0.01mg / cm 2 Up to 0.12mg / cm 2 or 0.01mg / cm 2 Up to 0.06mg / cm 2 ), wherein the abrasion resistance is measured according to the test method described below; and an elongation at break (%) greater than 100% (alternatively, greater than 120%, greater than 140%, greater than 160%, or in the range of 110% to 200%, 120% to 200%, 140% to 200%, or 160% to 200%) in the machine direction (MD) at 20 gsm nonwoven, wherein the elongation at break is measured according to the test method described below.

[0068] For example, the nonwoven according to the embodiments disclosed herein may have a tensile strength of greater than 11.0 N / 1 inch in the machine direction (MD) at 20 gsm of the nonwoven, and an elongation at break (%) greater than 100% in the machine direction (MD) at 20 gsm of the nonwoven. As another example, the nonwoven according to the embodiments disclosed herein may have a tensile strength of greater than 11.0 N / 1 inch in the machine direction (MD) at 20 gsm of the nonwoven, and a tensile strength of less than 0.18 mg / cm in the machine direction (MD) at 20 gsm of the nonwoven. 2 As yet another example, the nonwoven according to the embodiments disclosed herein may have a tensile strength of greater than 11.0 N / 1 inch in the machine direction (MD) at 20 gsm of the nonwoven; an elongation at break (%) greater than 100% in the machine direction (MD) at 20 gsm of the nonwoven; and a tensile strength of less than 0.18 mg / cm in the machine direction (MD) at 20 gsm of the nonwoven. 2 wear resistance.

[0069] The nonwoven formed from the bicomponent fibers disclosed herein has an elution curve achieved via an improved comonomer composition distribution (ICCD) procedure at 40.0°C to 68.0°C (WT 40℃-68℃ ), wherein the weight percent at a temperature range of 40.0°C to 68.0°C on an elution curve achieved via ICCD can be measured according to the test method described below. All individual values ​​and subranges of at least 12 weight percent are disclosed and included herein. For example, the nonwoven has an elution curve of 40.0°C to 68.0°C (WT 40℃-68℃ ), wherein the weight percent at a temperature range of 40.0°C to 68.0°C on an elution curve achieved via ICCD can be measured according to the test method described below.

[0070] The nonwoven formed from the bicomponent fibers disclosed herein has an elution curve achieved via an improved comonomer composition distribution (ICCD) procedure at 40.0°C to 65.0°C (WT 40℃-65℃), wherein the weight percent at a temperature range of 40.0°C to 65.0°C on an elution curve achieved via ICCD can be measured according to the test method described below. All individual values ​​and subranges of at least 6 weight percent are disclosed and included herein. For example, the nonwoven has an elution curve of 40.0°C to 65.0°C (WT 40℃-65℃ ), wherein the weight percent at a temperature range of 40.0°C to 65.0°C on an elution curve achieved via ICCD can be measured according to the test method described below.

[0071] The nonwoven formed from the bicomponent fibers disclosed herein has an elution curve achieved via an improved comonomer composition distribution (ICCD) procedure at 40.0°C to 60.0°C (WT 40℃-60℃ ), wherein the weight percent at a temperature range of 40.0°C to 60.0°C on an elution curve achieved via ICCD can be measured according to the test method described below. All individual values ​​and subranges of at least 2 weight percent are disclosed and included herein. For example, the nonwoven has an elution curve of 40.0°C to 60.0°C (WT 40℃-60℃ ), wherein the weight percent at a temperature range of 40.0°C to 60.0°C on an elution curve achieved via ICCD can be measured according to the test method described below.

[0072] Test Method

[0073] density

[0074] Density is measured according to ASTM D-792 and is expressed in grams / cm 3 (g / cm 3 )express.

[0075] Melt index (I2)

[0076] Melt index (I2) may be measured according to ASTM D 1238 at 190 degrees Celsius and 2.16 kg, and is expressed in grams eluted per 10 minutes (g / 10 min).

[0077] Conventional Gel Permeation Chromatography (Conventional GPC)

[0078] The chromatographic system consists of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven chamber is set to 160°C, and the column chamber is set to 150°C. The columns used are 4 Agilent "mixed A" 30cm 20 micron linear mixed bed columns. The chromatographic solvent used is 1,2,4-trichlorobenzene and contains 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen bubbling. The injection volume used is 200 microliters, and the flow rate is 1.0 ml / min.

[0079] The calibration of the GPC column set was performed with at least 20 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000 g / mol, and arranged in 6 "cocktail" mixtures with at least ten times intervals between individual molecular weights. These standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000 g / mol, polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent, while for molecular weights less than 1,000,000 g / mol, polystyrene standards were prepared at 0.05 grams in 50 milliliters of solvent. The polystyrene standards were dissolved at 80°C by gentle stirring for 30 minutes. The polystyrene standard peak molecular weight is converted to ethylene / α-olefin interpolymer molecular weight using the following equation (as described by Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):

[0080] M 聚乙烯 =A×(M 聚乙烯 ) B (Equation 1)

[0081] Where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.

[0082] A fifth order polynomial was used to fit the corresponding ethylene / α-olefin interpolymer-equivalent calibration points.A small adjustment was made to A (from approximately 0.39 to 0.44) to correct for column resolution and band broadening effects such that the NIST standard NBS 1475 was obtained at a molecular weight of 52,000 g / mol.

[0083] Total plate counts for the GPC column set were performed with eicosane (prepared as 0.04 g in 50 mL TCB and dissolved for 20 minutes with gentle stirring). Plate counts (Equation 2) and symmetry (Equation 3) were measured with 200 microliter injections according to the following equations:

[0084]

[0085] Where RV is the retention volume in milliliters, Peak Width is in milliliters, Peak Max is the maximum height of the peak, and Half Height is half the height of Peak Max.

[0086]

[0087] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum position of the peak, tenth height is one tenth the height of the peak maximum, and where post-peak refers to the tail of the peak at a later retention volume than the peak maximum, and where pre-peak refers to the front of the peak at an earlier retention volume than the peak maximum. The plate count of the chromatographic system should be greater than 22,000, and the symmetry should be between 0.98 and 1.22.

[0088] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml and the solvent (containing 200 ppm BHT) was added to a septum-capped vial previously sparged with nitrogen via the PolymerChar high temperature autosampler. The samples were dissolved at 160°C for 3 hours under "low speed" shaking.

[0089] M n(GPC) 、M w(GPC) and M z(GPC) The calculations are based on GPC results using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer according to Equations 5a-5c, using the PolymerChar GPCOne TM Software, the baseline-subtracted IR chromatogram (IR i ) and the ethylene / α-olefin interpolymer equivalent molecular weight (M in g / mol) obtained from the narrow standard calibration curve at point i according to Equation 1 聚乙烯,i ). Subsequently, the GPC molecular weight distribution (GPC-MWD) diagram (wt GPC (lgMW) versus lgMW, where wt GPC (1 g MW) is the weight fraction of interpolymer molecules having a molecular weight of 1 g MW). Molecular weight is measured in g / mol, and wt GPC(lgMW) follows Eq. 4.

[0090] ∫wt GPC (lg MW)d lg MW = 1.00 (Equation 4)

[0091] Number average molecular weight M n(GPC) , weight average molecular weight M w(GPC) and z-average molecular weight M z(GPC) It can be calculated according to the following equation.

[0092]

[0093]

[0094]

[0095] To monitor deviations over time, a flow marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) was used to linearly correct the pump flow rate for each sample (Flow Rate (Nominal)) by comparing the RV of the corresponding decane peak in the sample (RV (FM Sample)) with the RV of the decane peak in the narrow standard calibration (RV (FM Calibrated)). It was then assumed that any changes in the decane marker peak time were related to linear changes in the flow rate (Flow Rate (Effective)) throughout the run. To facilitate the highest accuracy in the RV measurement of the flow marker peak, a least squares fitting procedure was used to fit the peak of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated according to Equation 6. Processing of the flow marker peak was performed via the PolymerChar GPCOne TM Software complete. An acceptable flow rate correction is such that the effective flow rate should be within 0.5% of the nominal flow rate.

[0096] Flow rate 有效 = Flow rate 标称 ×(RV(FM 校准 ) / RV(FM 样品 )) (Equation 6)

[0097] Improved Comonomer Composition Distribution (ICCD)

[0098] Improved comonomer composition distribution (ICCD) measurements were performed using a Crystallization Elution Fractionator (CEF) (PolymerChar, Spain) equipped with an IR-5 detector (PolymerChar, Spain) and a two-angle light scattering detector model 2040 (Precision Detector, currently from Agilent Technologies). The ICCD column was packed with gold-coated nickel particles (Bright 7GNM8-NiS, Nippon Chemical Industrial Co., Ltd.) in a 15 cm (length) x 1 / 4" (ID) stainless steel tube. Co.)). According to the reference (Cong, R.; Parrott, A.; Hollis, C.; Cheatham, M. WO2017040127A1, which is incorporated herein by reference), the column was filled and conditioned using a slurry method. The final pressure of the trichlorobenzene (TCB) slurry filling was 150 bar. The column was installed just before the IR-5 detector in the detector oven. Ortho-dichlorobenzene (ODCB, 99% anhydrous or industrial grade) was used as the eluent. Silica gel 40 (particle size 0.2 mm to 0.5 mm, catalog number 10181-3) was obtained from EMD Chemicals and can be used to dry the ODCB solvent. The ICCD instrument is equipped with a nitrogen (N2) Automatic sampler with purge function. ODCB was bubbled with dry N2 for one hour before use. Sample preparation was performed with an automatic sampler at 4 mg / ml (unless otherwise specified) at 160°C under oscillation for 1 hour. The injection volume was 300 μl. The temperature profile of the ICCD was: crystallization from 105°C to 30°C at 3°C / min, then thermal equilibrium at 30°C for 2 minutes (including the elution time of the soluble fraction set to 2 minutes), followed by heating from 30°C to 140°C at 3°C / min. The flow rate during elution was 0.50 ml / min. Data was collected at one data point per second. Column temperature calibration can be performed by using a reference material linear homopolymer polyethylene (with zero comonomer content, a melt index (I2) of 1.0 g / 10 min, a polydispersity M w(GPC) / M n(GPC)It was measured by conventional gel permeation chromatography as a mixture of approximately 2.6, 1.0 mg / ml) and eicosane (2 mg / ml) in ODCB. ICCD temperature calibration consists of the following four steps: (1) calculating a delay volume defined as the measured eicosane peak elution temperature minus a temperature offset of 30.00°C; (2) subtracting the temperature offset of the elution temperature from the ICCD raw temperature data (it should be noted that this temperature offset varies with experimental conditions, such as elution temperature, elution flow rate, etc.); (3) creating a linear calibration line that converts elution temperatures between 30.00°C and 140.00°C, such that the linear homopolymer polyethylene reference has a peak temperature at 101.0°C and eicosane has a peak temperature at 30.0°C; and (4) for the soluble fraction measured isothermally at 30°C, linearly extrapolating the elution temperatures below 30.0°C by using an elution heating rate of 3°C / min according to reference (Cerk and Cong et al., US9,688,795, which is incorporated herein by reference).

[0099] Weight percentage determination on ICCD elution curve

[0100] A single baseline is subtracted from the IR measurement signal to create a relative mass-elution plot that starts and ends with zero relative mass at its lowest and highest elution temperatures (usually between 35°C and 119°C). For convenience, this is expressed as a normalized amount relative to a total area equal to 1. In the relative mass-elution plot from the ICCD, the weight fraction (w) at each temperature (T) can be obtained. T (T)) (the weight fraction can be converted into weight percentage). T (T) vs. T) is from 35.0°C to 119.0°C when there is a temperature step increase of 0.200°C in the ICCD and is as follows:

[0101]

[0102] Weight fraction (WT 较低T-较高T ) can be obtained by calculating w over the temperature range of interest according to the following equation: T (T) Integrate the T curve to calculate:

[0103]

[0104] Tensile Strength and Elongation at Break % Test Method

[0105] For tensile testing, 20 grams per square meter (gsm) of nonwoven fabric was cut into 1 inch × 8 inch rectangular strips in the machine direction (MD) to use an Instron tensile tester for tensile testing. These strips were tested at a test speed of 300 mm / min at an initial clamp to clamp distance (L0) of 76.2 mm. The nonwoven tensile strength in Newton / 1 inch (N / 1 inch width) was measured under peak force. Under peak load, the clamp to clamp distance (L) was read, and elongation at break (%) was reported as (L-L0) / L0 × 100%. The average value of 5 samples was reported.

[0106] Abrasion resistance test method

[0107] The abrasion resistance of the example nonwoven can be measured using the Sutherland ink friction tester. Before testing, the sample of the 20gsm nonwoven was cut into a rectangular strip of 12.5cm×5cm and conditioned at 73℉+ / -2 and constant relative humidity for at least four hours. Then the 320-grit aluminum oxide cloth sandpaper of the rectangular strip of 12.5cm×5cm was installed on the Sutherland ink friction tester. Then the sample was weighed to the nearest 0.01mg and installed on the tester. Afterwards, a 2-pound weight was attached to the Sutherland ink friction tester, and the tester was run for 20 cycles at a rate of 42 cycles per minute. Adhesive tape was used to remove loose fibers, and the sample was reweighed to determine the amount of material loss. Abrasion resistance is defined as the weight of material loss divided by the size of the wear area. The unit of abrasion resistance is mg / cm 2 The average of 5 samples is reported.

[0108] Fiber Denier Measurement

[0109] Fiber diameters were measured via optical microscopy. Denier (defined as the weight of 9000 meters of such fiber) was calculated based on the density of each polymer component and the fiber diameter.

[0110] Filament speed measurement

[0111] The filament speed is calculated based on the following equation:

[0112] Filament speed (m / min) = throughput (g / min) / denier (g / 9000m) * 9,000 (Equation 9).

[0113] Differential Scanning Calorimetry (DSC)

[0114] Differential scanning calorimetry is used to measure the highest peak melting temperature (Tm) and the highest peak crystallization temperature (Tc) according to ASTM D3895-14. About 0.5 gram of sample is molded into film through 10 seconds-15 seconds compression at 25,000psi and 190 degrees Celsius. Weigh 5mg to 8mg sample and place the sample in DSC aluminum pan, wherein the lid is crimped on the pan to ensure a closed atmosphere. During the test, a nitrogen purge gas flow of 50ml / min is used.

[0115] The thermal characteristics of the sample were determined by ramping the sample temperature up and down to generate a heat flow versus temperature curve. For cooling and secondary heating information, the sample was heated to 150 degrees Celsius at a rate of 10 degrees Celsius / min and held isothermally for 5 minutes. The sample was then cooled to -40 degrees Celsius at a rate of 10 degrees Celsius / min, held isothermally for 5 minutes, and then heated to 150 degrees Celsius at a rate of 10 degrees Celsius / min.

[0116] Record a cooling curve and a second heating curve. Analyze the cooling curve by setting a baseline endpoint from the start of crystallization to -20°C. Analyze the heating curve by setting a baseline endpoint from -20°C to the end of melting. The values ​​determined are the highest peak melting temperature (Tm) and the highest peak crystallization temperature (Tc). The highest peak melting temperature (Tm) is reported based on the second heating curve. The highest peak crystallization temperature (Tc) is determined based on the cooling curve.

[0117] Example

[0118] Example of Production of Ethylene / α-Olefin Interpolymers

[0119] Polymer 1 (Poly. 1), Polymer 2 (Poly. 2), and Polymer 3 (Poly. 3), (which are ethylene / α-olefin interpolymers) were prepared according to the following process and table.

[0120] All raw materials (monomers and comonomers) and process solvents (narrow boiling range high purity isoparaffin solvent, Isopar-E) were purified with molecular sieves before introduction into the reaction environment. Hydrogen was supplied under pressure in high purity grades without further purification. The reactor monomer feed stream was pressurized to greater than the reaction pressure via a mechanical compressor. The solvent and comonomer (if present) feeds were pressurized to greater than the reaction pressure via a pump. The various catalyst components were manually diluted in batches with purified solvents and pressurized to greater than the reaction pressure. All reaction feed streams were measured with mass flow meters and independently controlled with computer automated valve control systems.

[0121] The reactor configuration was either single reactor operation or dual series reactor operation as specified in Tables 2A and 2B below.

[0122] A single reactor system or a dual reactor system in a series configuration is used. Each reactor is a continuous solution polymerization reactor consisting of a non-adiabatic isothermal circulation loop reactor full of liquid simulating a continuous stirred tank reactor (CSTR) with heat removal. All fresh solvents, monomers, comonomers (if present), hydrogen and catalyst component feeds can be independently controlled. The temperature of the total fresh feed stream (solvent, monomer, comonomer [if present] and hydrogen) entering each reactor is usually controlled between 15°C and 50°C to maintain a single solution phase by passing the feed stream through a heat exchanger. The total fresh feed entering each polymerization reactor is injected into the reactor at two locations, wherein there is an approximately equal reactor volume between each injection location. The fresh feed is controlled by having each injector receive half of the total fresh feed mass flow rate. The catalyst component is injected into the polymerization reactor through an injection nozzle to introduce the component into the center of the reactor flow. The main catalyst component feed is controlled by a computer to maintain the reactor monomer conversion at a specified value. The co-catalyst component is fed based on the calculated specified molar ratio with the main catalyst component. Immediately following each reactor feed injection location, the feed stream is mixed with the circulating polymerization reactor contents using static mixing elements. The contents of each reactor are continuously circulated through a heat exchanger which is responsible for removing most of the heat of reaction and where the temperature on the coolant side is responsible for maintaining an isothermal reaction environment at a specified temperature. Circulation around each reactor loop is provided by a pump.

[0123] In a dual series reactor configuration, the effluent from the first polymerization reactor (containing solvent, monomer, comonomer [if present], hydrogen, catalyst components and polymer) leaves the first reactor loop and is added to the second reactor loop. In all reactor configurations, the final reactor effluent (the second reactor effluent of the dual series or the single reactor effluent) enters a zone where a suitable reagent (water) is added and reacted with the suitable reagent to deactivate the final reactor effluent. At this same reactor outlet position, other additives are added for polymer stabilization (e.g., antioxidants suitable for stabilization during extrusion and manufacturing, including 3,5-di-tert-butyl-4-hydroxyhydrocinnamic acid octadecyl ester, tetra(methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate))methane and tris(2,4-di-tert-butyl-phenyl)phosphite).

[0124] After catalyst deactivation and addition of additives, the reactor effluent enters a devolatilization system where polymer is removed from non-polymer streams. The separated polymer melt is pelletized and collected. The non-polymer streams pass through various devices that separate most of the ethylene removed from the system. Most of the solvent and unreacted comonomer (if present) are recycled back to the reactor after passing through a purification system. A small amount of solvent and comonomer (if present) are purged from the process.

[0125] Figure 1 and Figure 2 The reactor stream feed data flow is graphically depicted, corresponding to the values ​​in Table 2A and Table 2B for the produced polymers. The data is presented so that the complexity of the solvent recycle system is taken into account, and the reaction system can be more simply handled as a once through flow diagram.

[0126] Table 1 - Catalyst components

[0127]

[0128] Table 2A—Poly.3 generation configuration

[0129]

[0130]

[0131] Table 2B - Generation configuration of Poly.1 and Poly.2

[0132]

[0133]

[0134] The following ethylene / α-olefin interpolymers were also used in the examples.

[0135] Poly.4 is ASPUN TM 6850A, an ethylene / α-olefin interpolymer commercially available from The Dow Chemical Company, Midland, Michigan.

[0136] Poly.5 is ASPUN TM 6835A, an ethylene / α-olefin interpolymer commercially available from The Dow Chemical Company, Midland, Michigan.

[0137] Poly.6 is ASPUN TM Dow® 6000, an ethylene / α-olefin interpolymer commercially available from The Dow Chemical Company, Midland, Michigan.

[0138] Poly.7 is DOWLEX TM 2517, an ethylene / α-olefin interpolymer commercially available from The Dow Chemical Company, Midland, Michigan.

[0139] Poly.8 is ELITE TM 5860, an ethylene / α-olefin interpolymer commercially available from The Dow Chemical Company, Midland, Michigan.

[0140] Table 3 below provides the melt index (I2), density, Mw of Poly.1 to Poly 8. (GPC) / Mn (GPC) , highest peak crystallization temperature (Tc) and highest peak melting temperature (Tm).

[0141] Table 3 - Properties of Poly.1 to Poly.8

[0142]

[0143] Fiber and nonwoven formation

[0144] Spunbond nonwovens are formed from bicomponent fibers and produced in a concentric core:sheath configuration of 50:50 (by weight percentage) on a single beam Reicofil 4 spunbond line. The core of the bicomponent fiber is an ethylene / alpha olefin interpolymer composition as reported in Table 4. The sheath is an ethylene / alpha olefin interpolymer composition that is the same or different from that reported in Table 4. The machine (Reicofil 4 spunbond line) is equipped with a spinneret with 7022 holes (6861 holes / m), and the outlet diameter of each hole is 0.6 mm. The L / D ratio of the hole is 4. The polymer melt temperature is set to about 230°C. The fibers are collected at the maximum sustainable chamber air pressure while maintaining stable fiber spinning and converting the fibers to a nonwoven of a target basis weight of 20gsm. The bonding of the web is performed between the engraved roll and the smooth roll at a roller gap pressure of 70daN / cm. The oil temperature of the engraved roll is adjusted to achieve optimal bonding without over-wrapping the nonwoven onto the roll. The oil temperature of the smooth roll was maintained 2°C lower than that of the engraved roll.

[0145] Example nonwovens formed from bicomponent fibers have been designated as inventive examples and comparative examples, as reported in Table 4. The fiber denier of the nonwovens, as well as the difference in the highest peak melting temperature (ΔTm), the difference in the highest peak crystallization temperature (ΔTc), and the difference in density (Δdensity) between the first region and the second region of the bicomponent fibers are reported in Table 5.

[0146] The combined first ethylene / α-olefin interpolymer and the second ethylene / α-olefin interpolymer on the ICCD elution curves of the nonwoven examples are reported in Table 6 at 40.0°C to 68.0°C (WT 40 ℃ -68 ℃)、40.0℃~65.0℃(WT 40 ℃ -65 ℃) and 40.0℃ to 60.0℃ (WT 40 ℃ -60 ℃) in a temperature range of 1000 ℃. Figure 3 , shows the ICCD elution curve of the nonwoven Example 2 of the present invention. The combined weight percentage of Poly.3 and Poly.8 of Example 2 of the present invention is 40.0℃ to 68.0℃ (WT 40 ℃ -68 ℃) is equal to 30% (as reported in Table 6). The two polymers in each region of the inventive nonwoven (Inventive Example 1 and Inventive Example 2) have a higher weight percentage on the ICCD elution curve, which contributes to the enhanced abrasion resistance, tensile strength and / or elongation at break properties (not being bound by theory).

[0147] Additional processing conditions for the nonwovens are reported in Table 7. Additional properties of the nonwovens are shown in Table 8. Compared to the comparative nonwovens (Comparative Examples 1-8), the inventive nonwovens (Inventive Example 1 and Inventive Example 2) have fine fiber deniers, while having higher ΔTm, ΔTc, and Δdensity, which contribute to enhanced abrasion resistance, tensile strength, and / or elongation at break properties (not being bound by theory).

[0148] Table 4 - Composition of bicomponent fibers used to form nonwovens

[0149]

[0150] Table 5 – Denier, ΔDensity, ΔTc and ΔTm Data

[0151]

[0152] Table 6 - ICCD data for nonwoven examples

[0153]

[0154]

[0155] Table 7 - Additional Conditions for Forming Nonwovens

[0156]

[0157] Table 8 - Nonwoven Properties: Reported in Newtons per inch (N / 1 inch) in the machine direction (MD) at 20 gsmTensile strength; mg / cm2 on MD at 20 gsm 2 Reported abrasion resistance; and elongation at break in MD at 20 gsm Length %.

[0158]

[0159] Unless expressly excluded or otherwise limited, each document cited herein (if any), including any cross-referenced or related patents or applications and any patent application or patent to which this application claims priority or benefit, is hereby incorporated by reference in its entirety. The citation of any document does not admit that it is prior art to any invention disclosed or claimed herein, or that it alone or in combination with any one or more other reference documents teaches, indicates or discloses any such invention. In addition, in the event that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to the term in this document shall prevail.

[0160] Although specific embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention be covered in the appended claims.

Claims

1. A bicomponent fiber, comprising: First and second regions; The first region comprises a first ethylene / α-olefin interpolymer having a highest peak melting temperature (Tm) less than 130° C. when measured by DSC; The second region comprises a second ethylene / α-olefin interpolymer having a density less than the density of the first ethylene / α-olefin interpolymer composition; wherein the highest peak melting temperature (Tm) of the first ethylene / α-olefin interpolymer is at least 3.5°C greater than the highest peak melting temperature (Tm) of the second ethylene / α-olefin interpolymer, wherein the highest peak melting temperature (Tm) is measured by DSC; wherein the first region and the second region are arranged in a core-sheath configuration; wherein the nonwoven formed from the bicomponent fibers comprises at least 12 weight percent of the combined first and second ethylene / α-olefin interpolymers on an elution curve achieved via an improved comonomer composition distribution (ICCD) procedure at a temperature range of 40.0°C to 68.0°C.

2. The bicomponent fiber of claim 1, wherein the first ethylene / α-olefin interpolymer has a maximum peak crystallization temperature (Tc) at least 3.5°C greater than the maximum peak crystallization temperature (Tc) of the second ethylene / α-olefin interpolymer, wherein the maximum peak crystallization temperature (Tc) is measured by DSC.

3. The bicomponent fiber of claim 1, wherein the density of the first ethylene / α-olefin interpolymer is at least 0.022 g / cm greater than the density of the second ethylene / α-olefin interpolymer. 3 .

4. The bicomponent fiber of claim 2, wherein the density of the first ethylene / α-olefin interpolymer is at least 0.022 g / cm greater than the density of the second ethylene / α-olefin interpolymer. 3 .

5. A nonwoven formed from a bicomponent fiber according to any one of claims 1 to 4, wherein the nonwoven has one or more of the following properties: a fiber denier equal to or less than 1.5 g / 9000 m; a tensile strength greater than 11.0 Newtons / inch in the machine direction at 20 gsm of the nonwoven; an elongation at break greater than 100% in the machine direction at 20 gsm of the nonwoven; and a strength less than 0.18 mg / cm in the machine direction at 20 gsm of the nonwoven. 2 wear resistance.

Citation Information

Patent Citations

  • Multi-layer, elastic articles

    US7498282B2

  • Ethylene / alpha-olefin interpolymers with improved pellet flowability

    US9688795B2

  • Chromatography of polymers with reduced co-crystallization

    WO2017040127A1

  • Three-dimensional loop material of bicomponent fiber

    WO2019083881A1